2011
DOI: 10.1097/sla.0b013e318211d849
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postoperative Handover Using a Tool to Assess Information Transfer and Teamwork

Abstract: This study has established the feasibility, validity, and reliability of a tool for evaluating postoperative handover. In addition to serving as an objective measure of postoperative handover, the tool can also be used to evaluate the efficacy of any intervention developed to improve this process. The study has also shown that postoperative handover is characterized by incomplete transfer of information and failures in the performance of key tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 23 publications
0
95
0
2
Order By: Relevance
“…This controversial discussion is beyond the scope of this study. Multiple studies have demonstrated the utility of tools to improve the quality of communication during handover, both in the operating room 31,32 and in other areas of medicine. 33,34 It would seem plausible that reducing errors during information transfer could lead to safer care.…”
Section: Discussionmentioning
confidence: 99%
“…This controversial discussion is beyond the scope of this study. Multiple studies have demonstrated the utility of tools to improve the quality of communication during handover, both in the operating room 31,32 and in other areas of medicine. 33,34 It would seem plausible that reducing errors during information transfer could lead to safer care.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The results of this study lead to the assumption that introducing a formal checklist to the process may decrease omissions of communication of critical information. Nagpal et al 6 developed a Postoperative Handover Assessment Tool (PoHAT) which reliably identifies deficiencies in the current methods of postoperative handover. In order to improve outcomes, in addition to formalising handover content, examining the quality of communication during handover is also an important aspect of quality control.…”
Section: Reported Anaesthesiologists Nursesmentioning
confidence: 99%
“…anaesthesiologist and nurse) quality of patient handover. With the notable exception of the recently published study by Nagpal et al, 6 previous studies investigating handover following surgery have used qualitative assessments only. 7,8 In addition, the evaluation of the transfer process was performed by a care provider involved in it, which may have led to observer bias.…”
Section: Introductionmentioning
confidence: 95%
“…The surgical history was frequently identified as crucial. 25,26 The current treatment was particularly important for the interview participants with a junior surgeon stating ''I make sure I initiate the first steps of the emergency management pathway prior to calling. ''…”
Section: Category 3: Clinical Detailsmentioning
confidence: 99%
“…The patient's vital signs and recent investigation reports were frequently mentioned. 25,27,28 The inclusion of salient points 28 while including sufficient detail 22,29 was identified as a difficult balancing act for junior doctors.…”
Section: Category 4: Problemmentioning
confidence: 99%